PEMBERIAN NUGGET IKAN TENGGIRI YANG DIFORTIFIKASI TEPUNG DAUN KELOR TERHADAP NILAI Z-SCORE TB/U dan BB/U PADA ANAK BALITA STUNTING - Haruni, Diah Sekar; Nuhriawangsa, Adi Magna Patriadi; Febrinasari, Ratih Puspita (Poltekkes Kemenkes Bandung, 2025)
Stunting is a nutritional problem caused by prolonged malnutrition. Mackerel and Moringa leaves are considered to have many health benefits on children growth. The study aimed to determine the effect of giving mackerel nuggets fortified with moringa flour on the nutritional status of stunted toddlers. The study took place in February and March of 2024, had a pre-post control group. The samples comprised 52 stunted children in West Nias, ranging in age from 24 to 59 months; toddlers with chronic illnesses and those with gluten and seafood allergies were excluded. Four groups were created from the samples: two control groups and two treatment groups. The treatment group received 100 grams of nuggets daily for 60 days, along with the collection of anthropometric data, including height and weight. Height-for-Age (HAZ) data was analyzed using Wilcoxon and Kruskal Wallis test while Weight-for-Age (WAZ) data used Paired T-test and One Way ANOVA test, then followed by a Post Hoc test. There was no significant difference in the increase in HAZ between treatments (p=0.741), but there was an effect of giving nuggets with the addition of moringa leaves at 3% (p=0.046) and 7% (p=0.007) on HAZ at 0,010 and 0,016 respectively. Weight-for-Age (WAZ) value increased differently for each treatment (p=0.001), with the most significant difference in the giving of nuggets fortified with 7% moringa leaves, namely 0,206. The conclusion of this study was that giving mackerel nuggets fortified with moringa flour increased HAZ and WAZ of stunted toddlers.